Modelling differential activation of knee joint extensors - Yeadon, M.; Wilson, C.; King, M. (International Journal of Computer Science in Sport, 2002)
The force exerted by a muscle is a function of the activation level and the maximum force which depends upon the muscle length and velocity of shortening. The relationship between muscle force and velocity may be described by a rectangular hyperbola in the concentric mode (Hill, 1938, Proc Royal Soc London B 126, 136-195) and by an inverted hyperbola in the eccentric phase. In voluntary knee extensions the activation is less than maximum in eccentric mode but reaches maximum in concentric mode (Westing et al., 1990, Acta Physiol Scand 140, 17-22). The aim of this study was to model this "differential activation" in order to calculate the maximum voluntary knee extensor torque over the full range of knee angular velocities.